Transcatheter arterial chemoembolisation (TACE) plus S-1 for the treatment of BCLC stage B hepatocellular carcinoma refractory to TACE - Wu-Kui Huang; Shu-Fa Yang; Li-na You; Mo Liu; Deng-Yao Liu; Peng Gu; Xi-Wen Fan (Contemporary Oncology)
Aim of the study : To assess the efficacy and safety of transcatheter arterial chemoembolization (TACE) plus S-1 for the treatment of Barcelona Clinic Liver Cancer (BCLC) Stage B HCC refractory to TACE. Material and methods : 26 patients meeting the eligibility criteria were enrolled. TACE was given on day 1, and S-1 on days 2–15. Tumor assessment was performed one month later according to mRECIST. The primary endpoints were TTP and OS. Results: Twenty-six patients received 176 TACE interventions in all. Fifteen patients of TACE plus S-1 received a total of 55 cycles of treatment of S-1, with a median of 4 cycles (range, 2–6). The total dose of S-1 was 6165 mg per day, while average was 120 mg (range, 100–125 mg) for 15 patients of TACE plus S-1. Median TTP and OS of TACE plus S-1 were 6 months (95% CI: 4.7–7.3) and 18 months (95% CI: 15.3–24.7), respectively, while TACE monotherapy was 4 months (95% CI: 2.4–5.6) and 13 months (95% CI: 9.8–16.2), respectively, and significant differences were detected. Though there were higher DCRs in patients of TACE plus S-1, no significant differences were detected. A total of 612 adverse events occurred during the course of the treatment, 367 in TACE plus S-1 and 245 in TACE mono-therapy. There were significant differences to anorexia and nausea, but they were tolerable. Conclusions : TACE plus S-1 in the present analysis was tolerable and associated with an interesting TTP and OS. TACE plus S-1 may be used as a new treatment method to BCLC Stage B HCC refractory to TACE.